2018
DOI: 10.1002/ese3.199
|View full text |Cite
|
Sign up to set email alerts
|

Robust control design for air breathing proton exchange membrane fuel cell system via variable gain second‐order sliding mode

Abstract: The nonlinear and time‐dependent characteristic and unknown modeling uncertainty of proton exchange membrane fuel cell (PEMFC) such as complex electro‐chemical, thermal, and fluid mechanic phenomena make its controller design quite challenging. In this paper, a controller based on a super twisting algorithm (STA) with variable gains is proposed to control the air breathing system of PEMFC. The strategy includes regulating the oxygen excess ratio (λnormalO2) for preventing the stack oxygen starvation and mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The stator of a permanent magnet motor uses toroidal windings. While reducing the length of the motor's end, it can also increase the cooling area of the stator windings so that the stator windings are directly cooled by the airflow, improving the cooling efficiency [12]. The ventilation cooling system structure of the high-speed permanent magnet synchronous traction motor discussed in this study is shown in Fig.…”
Section: Fluid Field Analysis Of High-speed Permanent Magnet Synchronous Traction Motormentioning
confidence: 99%
“…The stator of a permanent magnet motor uses toroidal windings. While reducing the length of the motor's end, it can also increase the cooling area of the stator windings so that the stator windings are directly cooled by the airflow, improving the cooling efficiency [12]. The ventilation cooling system structure of the high-speed permanent magnet synchronous traction motor discussed in this study is shown in Fig.…”
Section: Fluid Field Analysis Of High-speed Permanent Magnet Synchronous Traction Motormentioning
confidence: 99%
“…However, the low durability of PEMFC is still an obstacle to large-scale commercialization. [5][6][7] Numerous studies have reported deterioration mechanisms, accelerated stress tests (AST), and mitigation strategies during the last decade. In automotive applications, the operating conditions accelerate the degradation of the system relative to stationary applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sliding mode control (SMC) is a wellknown non-linear control scheme, has the capability to deal with non-linear systems with unknown uncertainties and disturbance, besides has less sensitivity to the system's parameters variations [20]. Several control structures and observers based on SMC were developed for PEMFC air supply system, among them, super twisting SMC [21,22], adaptive super twisting SMC [23], highorder SMC [24] and adaptive high-order SMC [25]. In addition, finite time state observer based-control via high-order sliding mode (HOSM) was designed to estimate and control the oxygen excess ratio [26] and highorder sliding mode observer based-fuel delivery control was proposed in Chen et al [2].…”
Section: Introductionmentioning
confidence: 99%